Antecedents, consequences and moderators of ambidextrous behaviours among frontline employees. Issue 8 (19th September 2016) - Kao, Ya-Ling; Chen, Ching-Fu
Abstract : Purpose: The demand for efficient and flexible workers is growing in the service industry, with the promise of enhanced revenue generation and customer retention. The purpose of this paper is to investigate the antecedents (i.e. intrinsic motivation (IM)) and consequences (i.e. service performance (SP)) of front line employees' ambidextrous behaviours, as well as the moderating roles of a proactive personality (PP), emotional intelligence (EI) and extrinsic reward (ER) in the IM-individual ambidexterity (IA) relationship. Design/methodology/approach: A self-administered questionnaire was designed to collect empirical data from 205 flight attendants working at a Taiwanese airline company. Hierarchical regression analysis is used to test the proposed relationships and estimate factor affecting employees' SP. Findings: The results confirm that IM is positively related to ambidextrous behaviour, which in turn improves SP. EI positively moderates the relationship between IM and IA, while a PP and ER negatively moderate it. Practical implications: This paper entails useful implications for service providers to better understand front line employees' ambidextrous behaviours and determine effective recruitment and reward management strategies that reflect the differing employee characteristic. Originality/value: This study addresses the important issue of ambidextrous behaviours in a service-oriented context by examining whether and how PP, EI and ER moderate the relationships among IM, IA and SP.